Roger Crab and the rhetoric of reclusion - Tanner, Rory (University of Ottawa (Canada), 2008)
Prophet, pamphleteer, and hermit, Roger Crab (c.1616-1680) stands out from the sectarian tumult of mid-seventeenth century London as a zealous religious independent and a noteworthy oppositional figure. This study describes Crab's brief publication career as shaping a "rhetoric of reclusion," identifying in his work the distinct patterns of self-representation intended to free a purportedly divine message from the damaging influences of printers and booksellers, hireling ministers, and even the authorial self. Crab writes against the untoward mediation of his own text, but also against such interference with other sacred text. Beyond reclusion, the hermit's task proves one of reclamation. He seeks through publication and public attestation to reclaim the word of God from wayward church interpretation and from sectarian misappropriation.
Keywords: Biography.; Religion, History of.; Literature, English.